(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The main objective of this investigation was to formulate Fluconazole microsponge by quasi emulsion solvent diffusion technique in order to provide sustained release. Microsponge was formulated by quasi emulsion solvent diffusion technique with varied drug–polymer ratios. Ethyl cellulose and Eudragit L-100 was used as a polymers and polyvinyl alcohol was used as a surfactant for the preparation of external phase. The prepared microsponges were characterized by Fourier transform infrared spectroscopy, particle size analysis, and evaluated for pH, spreadability, viscosity, surface morphology, drug content, entrapment efficiency, in vitro drug release, skin irritation test, antifungal activity as well. The formulated microsponges are spherical with a porous surface and 6.8 μm of mean particle size. The microsponges were then integrated into the carbopol gel. The In vitro drug release results showed that microsponges with 1:1 drug–polymer ratios were more effective to make a prolonged drug release of 89.318 % at the end of 8 hours. Consequently the formed microsponge-based gel of fluconazole would be a confident decision for formal treatment for protected and powerful treatment of fungal infections.